1977
DOI: 10.3109/00498257709035794
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Fate of Prazosin

Abstract: 1. [2-14C]Prazosin is rapidly distributed into tissues of the dog including heart, lung and vascular tissues. 2. Urinary excretion by rats and dogs is low, biliary secretion being the major route of elimination. 3. Biotransformation of prazosin in the rat and dog occurs primarily by 6- or 7-O-dealkylation and subsequent glucuronide formation, and to a lesser extent via N-dealkylation. 4. Preliminary metabolic studies in man indicate a pattern of metabolites similar to that observed in dogs and rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 2 publications
2
33
0
Order By: Relevance
“…The former drug had to be given at very high doses (16-32 mg/kg) in order to pass the blood-brain barrier in these animals. (The low doses of prazosin generally used in behavioral research (0.5-2.0 mg/ kg) did not significantly reduce ex vivo a 1 -binding in the cerebral cortex of our mice (male Swiss Webster) in support of similar findings by others for the mouse (Lindroos et al, 1984) and dog (Taylor et al, 1977).) A similar and nearperfect correlation was obtained again between loss of a 1 -binding sites and loss of active behavior, which made it virtually certain that these receptors controlled behavioral activity in this species.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitysupporting
confidence: 90%
“…The former drug had to be given at very high doses (16-32 mg/kg) in order to pass the blood-brain barrier in these animals. (The low doses of prazosin generally used in behavioral research (0.5-2.0 mg/ kg) did not significantly reduce ex vivo a 1 -binding in the cerebral cortex of our mice (male Swiss Webster) in support of similar findings by others for the mouse (Lindroos et al, 1984) and dog (Taylor et al, 1977).) A similar and nearperfect correlation was obtained again between loss of a 1 -binding sites and loss of active behavior, which made it virtually certain that these receptors controlled behavioral activity in this species.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitysupporting
confidence: 90%
“…Product ions at m/z 233 and 190 were 14 Da less than the corresponding ions at m/z 247 and 204 for prazosin, supporting a single demethylation event on the amino-dimethoxyquinazoline group. Previously it was reported that the major demethylated metabolite in vivo was 6-desmethyl prazosin (Taylor et al, 1977), and we observed that the abundance of M3 was larger than M6. Therefore, M3 and M6 were tentatively identified as 6-desmethyl and 7-desmethyl prazosin, respectively.…”
Section: Metabolism Of Prazosin In Nadph-and Udpga-fortifiedmentioning
confidence: 49%
“…One objective of this work was to use current in vitro methodology and analytical tools to study the metabolism of prazosin and to determine the correlation with in vivo data (Taylor et al, 1977;Piotrovskii et al, 1984). Further understanding prazosin metabolism remains relevant because of renewed interest in prazosin for PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ratio of adipose to lean tissue increases with age (Bender, 1964) it would not be unexpected to find lipophilic drugs demonstrating a greater VdSS in the elderly. Prazosin has, in fact, only modest lipophilic properties (Taylor et al, 1977) and its 40% greater Vdss in the elderly is presumably a reflection of this fact when viewed against the 200-300% changes seen with the far more lipophilic drug diazepam.…”
Section: Discussionmentioning
confidence: 99%